Insulator materials for interface passivation of Cu(In,Ga)Se2 thin films - Cunha, J. M. V. (2018)
In this work, Metal-Insulator-Semiconductor (MIS) structures were fabricated in order to study different types of insulators, namely, aluminum oxide (Al2O3), silicon nitride (Si3Nx) and silicon oxide (SiOx) to be used as passivation layers in Cu(In,Ga)Se2 (CIGS) thin film solar cells. The investigated stacks consisted of SLG/Mo/CIGS/insulator/Al. Raman scattering and Photoluminescence measurements were done to verify the insulator deposition influence on the CIGS surface. In order to study the electrical properties of the CIGS-insulator interface, capacitance vs. conductance and voltage (C-G-V) measurements were done to estimate the number and polarity of fixed insulator charges (Qf). The density of interface defects (Dit) was estimated from capacitance vs. conductance and frequency (C-G-f) measurements. This study evidences that the deposition of the insulators at high temperatures (300 ºC) and the use of sputtering technique cause surface modification on the CIGS surface. We found that, by varying the SiOx deposition parameters, it is possible to have opposite charges inside the insulator, which would allow its use in different device architectures. The material with lower Dit values was Al2O3 when deposited by sputtering.